Effects of modulating probiotics on greenhouse gas emissions and yield in rice paddies - Pao, Shang-Hung; Wu, Hewder; Hsieh, Hwey-Lian; Chen, Chang-Po; Lin, Hsing-Juh (Plant, soil and environment, 2025)
Rice serves as a crucial staple food for nearly half of the world’s population. However, rice paddies contribute remarkably to greenhouse gas (GHG) emissions. Prior studies often showed a trade-off between reducing GHG emissions and impairing rice yield. In this study, we explore the possibility of employing modulating probiotics to develop a win-win strategy for enhancing rice yields while reducing GHG emissions. Three paired plots of rice paddies were used in the field experiment during the spring growing season (from February to July 2022). Each pair of plots was divided into control and probiotic addition paddies to investigate the effects of modulating probiotic treatment on GHG emissions using the whole-plant chambers. Our results revealed notable reductions in GHG emissions and increases in rice yield with the probiotic treatment relative to the control. The probiotic treatment resulted in a 47.58% reduction in carbon dioxide (CO2) emissions, a 21.53% reduction in methane (CH4) emissions, and an impressive 88.50% reduction in nitrous oxide (N2O) emissions over the growing season. We also observed a 27.75% increase in rice yield with the probiotic treatment. These findings suggest that employing modulating probiotics has the potential to pave the way for mutually beneficial outcomes, enhancing rice productivity while mitigating the GHG emissions associated with rice cultivation.